ROS 2018
DOI: 10.20455/ros.2018.839
|View full text |Cite
|
Sign up to set email alerts
|

Brain Oxidative Stress and Neurodegeneration in the Ketamine Model of Schizophrenia during Antipsychotic Treatment: Effects of N-Acetylcysteine Treatment

Abstract: We aimed to investigate the effect of N-acetylcysteine (NAC) on brain oxidative stress and on the response to therapy with clozapine or haloperidol in the ketamine model of schizophrenia. Mice received intraperitoneal (i.p.) injections of either saline, ketamine (30 mg/kg), NAC (50 mg/kg), ketamine + NAC, ketamine + clozapine (1.5 mg/kg), ketamine + clozapine + NAC, ketamine + haloperidol (1.5 mg/kg), or ketamine + haloperidol + NAC daily for one week. Malondialdehyde (MDA), reduced glutathione (GSH), nitric o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 59 publications
(70 reference statements)
0
7
0
Order By: Relevance
“…As previously mentioned, oxidative disturbances are important mechanisms underlying schizophrenia. These mechanisms involve the production of reactive oxygen and nitrogen species resulting in lipid peroxidation (Abdel-Salam et al, 2018). In a previous study, we identified oxidative imbalance in the PFC and striatum of rats neonatally challenged with poly I:C that were influenced by sex (Monte et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…As previously mentioned, oxidative disturbances are important mechanisms underlying schizophrenia. These mechanisms involve the production of reactive oxygen and nitrogen species resulting in lipid peroxidation (Abdel-Salam et al, 2018). In a previous study, we identified oxidative imbalance in the PFC and striatum of rats neonatally challenged with poly I:C that were influenced by sex (Monte et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Level of GSH play an important role against SB‐induced oxidative stress. Moreover, the brain GSH depletion and oxidative stress have a potential role in cognitive impairment in psychiatric illnesses …”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress and free radical generation have been implicated in the pathogenesis of several brain disorders such as AD, Parkinson's disease, multiple sclerosis, schizophrenia, and autism . It has also been suggested that depletion of GSH, the main CNS antioxidant, as a result of increased oxidative stress, play important role in the decline of cognitive functions and disruption of short‐term spatial memory …”
Section: Introductionmentioning
confidence: 99%
“…[ 19,20 ] The role of reduced glutathione (GSH) in mopping reactive oxygen species (ROS) in the brain is a key mechanism of neuroprotection against cognitive decline. [ 21 ] Thus, targeting oxidative stress with strong antioxidants could be a promising approach to offer protection against oxidative stress and neurobehavioural impairments.…”
Section: Introductionmentioning
confidence: 99%